IMPLEMENTASI TOPSIS PADA SISTEM PENDUKUNG KEPUTUSAN PENERIMAAN BANTUAN DANA PENDIDIKAN SANTRI - Hammi, Moh Mufarijul; Latipah; Muchayan, Achmad (Antivirus : Jurnal Ilmiah Teknik Informatika, 2022)
Determining the recipients of the student education assistance fund, it is an effort made by the Al-Jihad Islamic Boarding School in Surabaya to improve the educational welfare of underprivileged students. The main focus for the determining potential recipients of education assistance funds is the accuracy of targeting the recipients. Many students with middle to lower economic status are the main reason for delaying the payment of sharia obligations. However, in reality preparations for the selection of prospective recipients of student aid funds are still being carried out with the criteria and readiness for what the status is. The problem is not right on target for the recipient. So, it is necessary to design a Decision Support System (DSS) to run this program as well as possible. This research uses a type of research model, namely Multi Criteria Decision Making (MCDM) which prioritizes assessment based on the desired criteria. The assessment criteria include: the income of the guardian of the santri in one month, the burden of family costs in one month, the number of relatives, and the length of time in line. To determine the weighting of the criteria using the Technique for Others Reference by Similarity to Ideal Solution (TOPSIS) method. Thus, the results of research that have been carried out using the TOPSIS method in determining prospective recipients of student educational assistance funds based on the criteria determined by the results of the preference value A1 with a value of 1 ranking 1, A2 with a value of 0.7913 ranking 2, A3 with a value of 0.6125 ranking 3.